Neurally mediated vasoconstriction is capable of decreasing skin blood flow during orthostasis in the heat-stressed human - Shibasaki, Manabu (Blackwell Science Inc, 2006)
Given the large increase in cutaneous vascular conductance (CVC) during whole-body heat stress, this vascular bed is important in the regulation of blood pressure during orthostatic stress. In this thermal state, changes in CVC are reported to be due to withdrawal of active vasodilator activity. The purpose of this study was to identify, contrary to the current line of thinking, whether cutaneous vasoconstrictor neural activity is enhanced and capable of contributing to reductions in CVC during an orthostatic challenge of heat-stressed individuals. Healthy normotensive subjects were pretreated, subcutaneously, with botulinum toxin A (BTX-A) to inhibit the release of neurotransmitters from cutaneous active vasodilator nerves. On the experimental day, microdialysis probes were placed in the BTX-A-treated site and in an adjacent untreated site. In protocol 1, internal temperature was elevated ∼0.7°C, followed by the application of lower body negative pressure (LBNP; −30 mmHg). LBNP reduced CVC at the BTX-A-treated sites (Δ4.2 ± 2.9%max), as well as at the control site (Δ9.8 ± 4.1%max). In protocol 2, after confirming the absence of cutaneous vasodilatation at the BTX-A-treated site during whole-body heating, CVC at this site was elevated to a similar level relative to the control site (55.4 ± 13.4 versus 60.7 ± 10.4%max, respectively) via intradermal administration of isoproterenol prior to LBNP. Similarly, when flow was matched between sites, LBNP reduced CVC at both the BTX-A-treated (Δ15.3 ± 4.6%max) and the control sites (Δ8.8 ± 5.6%max). These data suggest that the cutaneous vasoconstrictor system is engaged and is capable of decreasing CVC during an orthostatic challenge in heat-stressed individuals.